PLACENTAL GROWTH FACTOR AND CORONARY NEOANGIOGENESIS IN CORONARY HEART DISEASE - M. V. Tulikov; O. P. Shevchenko; A. O. Shevchenko; A. V. Gagayev; V. V. Pavlov (Klinicist)
Neoangiogenesis in coronary heart disease is a protective reaction aimed to improve ischemic myocardial perfusion, by increasing the number and size of arterial collaterals. Placental growth factor (PlGF) is one of the key peptides regulating angiogenic processes in atherosclerosis. In particular, a number of investigators have shown that injection of recombinant PlGF into the system or regional blood flow can stimulate neoangiogenesis. On the other hand, there is evidence confirming the involvement of PlGF in the progression of atherosclerosis and in the development of acute coronary syndrome. In this connection, the problem of investigating the efficiency and safety of possible use of PlGF preparations, as well as its place in the diagnosis of coronary heart disease and acute coronary syndrome remains urgent